1995
DOI: 10.1159/000126855
|View full text |Cite
|
Sign up to set email alerts
|

Interaction off αT3-1 Cells with Lactotropes and Somatotropes of Normal Pituitary in vitro

Abstract: A pituitary cell population of 14-day-old female rats, containing lactotropes and somatotropes but deprived of gonadotropes, was prepared by unit gravity sedimentation through a serum albumin gradient and allowed to reaggregate either as such or after mixing this population with cells of the gonadotropic αT3-1 cell line. In a perifusion system gonadotropin-releasing hormone (GnRH) had no effect on prolactin (PRL) and growth hormone (GH) release in the former aggregates but stimulated PRL release in the latter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Based upon morphological observations, as well as findings from re-aggregation studies, an important role for cell-cell communication for pituitary function and hormone release has long been suspected. For example, cup-shaped lactotrophs embrace and surround gonadotrophs in multiple species (Gregory et al, 2000;Hovarth et al, 1977;Tortonese et al, 1998), gonadotroph-conditioned medium evokes PRL secretion from cultured lactotrophs (Andries et al, 1995;Denef and Andries, 1983), application of a gonadotroph-specific secretagogue (GnRH) upregulates lactotroph output (Henderson et al, 2008), and gap junction-signaling is positively correlated with circulating PRL levels (Vitale et al, 2001). Whilst it is beyond the scope of the current review to discuss intrapituitary communication in detail (please refer to recent reviews from ours and other groups (Denef, 2008;Hodson et al, 2012a)), the important routes will nonetheless be highlighted within the context of endocrine cell networks.…”
Section: Intrapituitary Regulation Of Endocrine Cell Network Functionmentioning
confidence: 99%
“…Based upon morphological observations, as well as findings from re-aggregation studies, an important role for cell-cell communication for pituitary function and hormone release has long been suspected. For example, cup-shaped lactotrophs embrace and surround gonadotrophs in multiple species (Gregory et al, 2000;Hovarth et al, 1977;Tortonese et al, 1998), gonadotroph-conditioned medium evokes PRL secretion from cultured lactotrophs (Andries et al, 1995;Denef and Andries, 1983), application of a gonadotroph-specific secretagogue (GnRH) upregulates lactotroph output (Henderson et al, 2008), and gap junction-signaling is positively correlated with circulating PRL levels (Vitale et al, 2001). Whilst it is beyond the scope of the current review to discuss intrapituitary communication in detail (please refer to recent reviews from ours and other groups (Denef, 2008;Hodson et al, 2012a)), the important routes will nonetheless be highlighted within the context of endocrine cell networks.…”
Section: Intrapituitary Regulation Of Endocrine Cell Network Functionmentioning
confidence: 99%
“…In females, E2 exerts a negative feedback on LH release for the greater part of the ovarian cycle, at least in part through direct actions at the pituitary level. This inhibitory action is transiently reversed into marked facilitation of pituitary LH secretion during the mid-cycle LH surge (Knobil, 1988;Herbison, 1998;Kerdelhué et al, 2002;Moenter et al, 2003) The role of E2 in the GnRH-mediated regulation of LH release by pituitary gonadotrophs has been extensively investigated using primary pituitary cell cultures and isolated perifused pituitaries (Emons et al, 1989;Ortmann et al, 1992a;Ortmann et al, 1992b) However, gonadotrophs represent only 10-15% of the anterior pituitary cell population (Wang, 1988) It has been established that paracrine interactions between gonadotrophs and other pituitary cell types, including lactotrophs and somatotrophs, may influence basal or GnRH-induced LH secretion (Cheung, 1983;Denef and Andries, 1983;Andries et al, 1995;Gregory et al, 2004), hereby complicating data interpretation. The need for in vitro models to study estrogenic effects at the pituitary level is further emphasized by the increasing interest for the therapeutic use of phytoestrogens and the development of selective estrogen receptor modulators on the one hand and growing concern for potentially disrupting effects of chemical pollutants with estrogenic actions on reproductive function on the other hand (Eertmans et al, 2003) A c c e p t e d M a n u s c r i p t…”
Section: Introductionmentioning
confidence: 99%
“…The paracrine cross-talk with lactotrophs and somatotrophs was also confirmed by coaggregation of a lactotrophs/somatotroph population from 14-day-old rats with cells of the gonadotrophic cell line αT3-1 (101). It was found that GnRH induced a stimulation of PRL release and a dual effect on GH release, although the magnitude of the response was smaller than in normal pituitary.…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 70%
“…Mediation by paracrine factor(s) was indicated by the finding that medium conditioned by a highly enriched population of gonadotrophs cultured in the presence of GnRH, mimicked the effects of GnRH (120, 121). Also, medium conditioned by the gonadotroph precursor cell line αT3-1 contained material stimulating development of lactotrophs and inhibiting development of somatotrophs (101). Four substances with a selective mitogenic effect on lactotrophs were partially purified by high-performance liquid chromatography fractionation, whereas two other substances were isolated with antisomatotroph action (120, 121).…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 99%